Molecular and Biological Subtypes of Breast Cancer (Texas Journal of Medical Science, 2025)
Breast cancer is a heterogeneous disease characterized by diverse molecular and biological subtypes, which influence prognosis and treatment strategies. Identification of these subtypes through molecular profiling has significantly improved personalized therapy, leading to better clinical outcomes. This review provides an overview of the main molecular subtypes of breast cancer, their biological characteristics, and implications for patient management